Inactivation of SARS CoV-2 on porous and nonporous surfaces by compact portable plasma reactor - Choudhury, Bhaswati; Lednicky, John A.; Loeb, Julia C.; Portugal, Sherlie; Roy, Subrata (Frontiers in Bioengineering and Biotechnology, 2024)
We report the inactivation of SARS CoV-2 and its surrogate -Human coronavirus OC43 (HCoV-OC43), on representative porous (KN95 mask material) and nonporous materials (aluminum and polycarbonate) using a Compact Portable Plasma Reactor (CPPR). The CPPR is a compact (48 cm 3 ), lightweight, portable and scalable device that forms Dielectric Barrier Discharge which generates ozone using surrounding atmosphere as input gas, eliminating the need of source gas tanks. Iterative CPPR exposure time experiments were performed on inoculated material samples in 3 operating volumes. Minimum CPPR exposure times of 5-15 minutes resulted in 4 to 5 log reduction of SARS CoV-2 and its surrogate on representative material samples. Ozone concentration and CPPR energy requirements for virus inactivation are documented. Difference in disinfection requirements in porous and non-porous material samples is discussed along with initial scaling studies using the CPPR in 3 operating volumes. The results of this feasibility study, along with existing literature on ozone and CPPR decontamination, show the potential of the CPPR as a powerful technology to reduce fomite transmission of enveloped respiratory virus-induced infectious diseases such as COVID-19. The CPPR can overcome limitations of high temperatures, long exposure times, bulky equipment, and toxic residuals related to conventional decontamination technologies.